THE IMPACT OF MASS MEDIA ON THE SPIRITUAL AND MORAL FORMATION OF YOUTH - Rustam Akhundjanovich Begmatov (Web of Journals Publishing, 2025)
The article briefly describes the influence of mass media on the spiritual and moral formation of youth.
Keywords: Mass media, information security, openness of mass media, education of the younger generation, cultural-moral and spiritual values.